Study on Dried Fish Chips Mixed with River Weed Production by Using Different Ratio - MANYSOAT, Soutthanou; DUANGDALA, Visanaluck; PHASOUK , Amphone; SALITXAY, Timnoy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study was aimed to investigate basic recipe with addition of river weed at different ratio for making dried fish. The main ingredients of basic recipe consisted fish, river weed, and flour in 1:1:1 ratio. The method was commenced by preparing these ingredients, then mixed with additive ingredient before drying in the dry house in a period of 7 hours. After that they became ready to make ready-to-eat fish after frying. Then, they were optimized sensory with odor, flavor, and crispness. They were divided in to 3 treatments: T1, basic recipe in 1:1:1 ratio, T2 1:1.5:1 ratio, T3 1:2:1 ratio. The researchers investigated moisture content before and after frying each recipe. Total of 50 people were selected to conduct sensory evaluation. The result revealed that, the moisture content before frying of T1, T2, T3 were 7.37, 4.42, and 4.23%; respectively. In the meantime, the moisture content after frying was 2.09, 1.24, and 1.14%; respectively. The result of sensory evaluation showed that, the crispness, salts, spiciness, color, odor of mixed fish, river weed and sweetness of T2 were 7.20, 7.06, 6.76, 6.92, 7.52, 6.78, 6.62, 7.18 and 7.28; respectively from 9 point. Overall taste was more acceptable for T2 (1:1.5:1 ratio of fish, river weed, and flour). According to this result, T2 may be the most effective way to produce dry fish chip mixed with river weed.